Response of luteinizing hormone from columns of dispersed rat pituitary cells to a highly potent analogue of luteinizing hormone releasing hormone. - Yeo, T; Grossman, A; Belchetz, P; Besser, G (1981)
The response of LH from a perfused column of dispersed rat anterior pituitary cells to LH releasing hormone (LH-RH) and the analogue, D-Ser(But)6-desGly10-Proethylamide9-LH-RH (Hoe 766), was investigated. Dose-response curves showed non-parallelism between LH-RH and the analogue. but it was evident that the analogue was considerably more potent. After a single pulse of LH-RH, LH output returned to basal values in 8 min; this was prolonged to 20 min in the case of the analogue. During this 20 min the cells were refractory to pulses of LH-RH but pulses of the analogue maintained output of LH. During constant-dose perfusion with either synthetic LH-RH or the analogue, output of LH rapidly reached a peak and then gradually fell over several hours to approach baseline values. However, a pulse of 50 mmol potassium chloride/l was still able to release LH at this time. The data are consistent with the view that this analogue of LH-RH is highly potent and is strongly bound by the LH-RH receptor. Furthermore, since it desensitizes the LH-RH receptor, it appears that continued turnover of either LH-RH or the analogue at the receptor is necessary for output of LH to be maintained.